Enhancing OSCE preparedness with video exemplars in undergraduate nursing students. A mixed method study. (July 2017) - Massey, D.; Byrne, J.; Higgins, N.; Weeks, B.; Shuker, M.-A.; Coyne, E.; Mitchell, M.; Johnston, A.N.B.
Abstract: Background: Objective structured clinical examinations (OSCEs) are designed to assess clinical skill performance and competency of students in preparation for 'real world' clinical responsibilities. OSCEs are commonly used in health professional education and are typically associated with high levels of student anxiety, which may present a significant barrier to performance. Students, including nursing students, have identified that flexible access to exemplar OSCEs might reduce their anxiety and enable them to better prepare for such examinations. Aim: To implement and evaluate an innovative approach to preparing students for OSCEs in an undergraduate (registration) acute care nursing course. Method: A set of digitized OSCE exemplars were prepared and embedded in the University-based course website as part of usual course learning activities. Use of the exemplars was monitored, pre and post OSCE surveys were conducted, and qualitative data were collected to evaluate the approach. OSCE grades were also examined. Findings: The online OSCE exemplars increased self-rated student confidence, knowledge, and capacity to prepare and provided clarity around assessment expectations. OSCE exemplars were accessed frequently and positively received; but did not impact on performance. Conclusion: Video exemplars aid student preparation for OSCEs, providing a flexible, innovative and clear example of the assessment process. Video exemplars improved self-rated student confidence and understanding of performance expectations, leading to increased engagement and reduced anxiety when preparing for the OSCE, but not overall OSCE performance. Such OSCE exemplars could be used to increase staff capacity and improve the quality of the student learning experience. Highlights: Clinical skills developed in a simulated environment help prepare undergraduate nurses students for real world experiences. OSCEs are stressful and create significant anxiety that may impact on learning Video exemplars of OSCE may help to prepare students and reduce anxiety and promote learning.